Development of Solar Dryer with Electrical Energy Backup for Hygienic Drying of Fish and Fish Products - Nagori, Ankur; Joshi, P N; Ravishankar, C N (Fishery Technology, 2025)
Traditional sun drying methods under open sun for preserving low value fishery as well as agricultural products have several disadvantages such as contamination of food products by dust, dirt, birds, animals and insects and spoilage due to rain, wind and moisture. To overcome the disadvantage of open sun drying, a solar dryer with alternate energy backup of electricity was designed and developed for drying fishes and fish products hygienically in hot and humid climatic conditions. An experimental study on solar drying of small prawns was carried out and result was analyzed for validation of drying unit to be developed for hygienic drying of fish using solar energy. The experimental trials on solar drying were conducted using food grade stainless steel (SS 304) trays, drying chamber and solar heat collecting panels under controlled climatic conditions. The time required for reducing the moisture content of prawn to 8.7% was 8 h in the solar dryer. Colour and texture of the dried prawns prepared in closed drying chamber was found to be better than product prepared by other traditional drying methods. The collection efficiency of solar heat collecting panels was found to be approximately 82% and the distribution of hot air temperature inside the drying chamber was found to be uniform throughout the experiment. The average tray temperature inside the drying chamber at full load was 49oC without any alternate energy backup. Water activity of dried prawns was found 0.6 and the drying rate was also calculated. Solar drying process was found to be hygienic and reliable with respect to product quality.